Perbedaan Pengetahuan, Sikap, dan Konsumsi Lemak Sebelum-Sesudah Penyuluhan Gizi dengan Media VitaNutriHealth pada Siswa dan Siswi Overweight di SMK Negeri 02 Kota Malang - Anggraini, Lutfiyah Zahra; Riyadi, Bastianus Doddy; Hadisuyitno, Juin; Tanu Komalyna, I Nengah (NUTRITURE JOURNAL, 2026)
Background: Overweight in adolescence is a significant nutritional problem because it may persist into adulthood and increase the risk of obesity-related comorbidities. High fat intake is one of the dietary factors contributing to excess body weight. Nutrition education through digital media such as VitaNutriHealth may improve nutrition knowledge, attitudes, and dietary behavior. Objective: This study aimed to determine changes in knowledge, attitudes, and fat intake before and after nutrition education using VitaNutriHealth among overweight students at SMK Negeri 02 Kota Malang. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 40 students selected through purposive sampling. The intervention included four weeks of nutrition education using the VitaNutriHealth application. Knowledge and attitudes were assessed using structured questionnaires, while fat intake was measured using a 24-hour dietary recall. Paired sample t-tests were used to analyze changes in knowledge and fat intake, while the Wilcoxon signed-rank test was used for attitude. Results: Knowledge scores increased from 73.25 ± 13.27 to 96.00 ± 5.90. The proportion of students with supportive attitudes increased from 40% to 65%. Mean fat intake decreased from 74.98 ± 2.33 g to 72.54 ± 2.22 g. All changes were statistically significant (p<0.001). Conclusion: Nutrition education using VitaNutriHealth may improve knowledge and attitudes and reduce fat intake among overweight students.